2020
DOI: 10.1177/0146167220916631
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analytic Use of Balanced Identity Theory to Validate the Implicit Association Test

Abstract: This meta-analysis evaluated theoretical predictions from balanced identity theory (BIT) and evaluated the validity of zero points of Implicit Association Test (IAT) and self-report measures used to test these predictions. Twenty-one researchers contributed individual subject data from 36 experiments (total N = 12,773) that used both explicit and implicit measures of the social–cognitive constructs. The meta-analysis confirmed predictions of BIT’s balance–congruity principle and simultaneously validated interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…The exception is that the association-strength interpretation is the only theoretical interpretation that can produce the novel predictions of BIT (Greenwald et al, 2002) that were described under the preceding Construct Validity heading. Consistent experimental confirmation of the BIT predictions (reviewed by Cvencek et al, 2021) favors the association-strength interpretation.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The exception is that the association-strength interpretation is the only theoretical interpretation that can produce the novel predictions of BIT (Greenwald et al, 2002) that were described under the preceding Construct Validity heading. Consistent experimental confirmation of the BIT predictions (reviewed by Cvencek et al, 2021) favors the association-strength interpretation.…”
Section: Discussionmentioning
confidence: 68%
“…The finding that the confound worked in different directions for men and women provided inspiration for balanced identity theory (BIT; Greenwald et al, 2002), which used a balance–congruity principle to predict relations among interrelated trios of measures of identity, self-esteem (or self-concept), and attitude (or stereotype). A meta-analysis recently reported by Cvencek et al (2021) found that the novel correlational predictions of BIT’s balance–congruity principle were consistently confirmed in 36 studies, involving 12,733 subjects, that had tested these predictions with both IAT and self-report measures.…”
Section: What Is Known About Implicit Biasmentioning
confidence: 76%
“…The implicit response is to simply ignore criticism and to make invalid claims about the construct validity of IATs ( Greenwald & Lai, 2020 ). For example, a 2020 article coauthored by Nosek, Greenwald, and Banaji (among others) claimed that “available evidence for validity of IAT measures of self-esteem is limited ( Bosson et al, 2000 ; Greenwald & Farnham, 2000 ), with some of the strongest evidence coming from empirical tests of the balance-congruity principle” ( Cvencek et al, 2020 , p. 191). This statement is as valid as Donald Trump’s claim that an honest count of votes would make him the winner of the 2020 election.…”
Section: Implicit Responsementioning
confidence: 99%
“…Even its creator is no longer sure what IATs measure. Whereas Banaji and Greenwald (2013) confidently described IATs as “a method that gives the clearest window now available into a region of the mind that is inaccessible to question-asking methods” (p. xiii), they now claim that IATs merely measure “the strengths of associations among concepts” ( Cvencek et al, 2020 , p. 187). This is akin to saying that an old-fashioned thermometer measures the expansion of mercury: It is true, but it has little to do with thermometers’ purpose of measuring temperature.…”
mentioning
confidence: 99%
“…Balanced identity theory has most typically been applied to examine the formation of implicit self-stereotypes (Cvencek et al, 2020) (Cvencek et al, 2020). For example, women's tendency to implicitly associate math more with men than women relates to women's tendency to associate math less with themselves (Nosek et al, 2002).…”
Section: Individual Processes and Experiences Create Gendered Cognitionsmentioning
confidence: 99%